Pengaruh Penerapan Sistem Informasi Manajemen Pendidikan dan Extreme Programming dalam Pengembangan Sistem Informasi Manajemen Pelayanan Publik - Wenang Perdana; Ines Heidiani Ikasari (Buletin Ilmiah Ilmu Komputer dan Multimedia, 2023)
This study examines the effect of the application of Management Information Systems (MIS) on public services in the Boronadu Sub-District Office of South Nias Regency and the application of educational SIMs in the learning process at SMP Negeri 9 Buru Regency, as well as the application of Extreme Programming in the development of public service SIMs in Sukarame District. This study involved a sample of 16 Boronadu sub-district office employees, and used observation, interview, and documentation techniques in collecting data at SMP Negeri 9 Buru District. The results of the study show that the application of SIM and information technology in education is very important to improve education services at SMP Negeri 9. In addition, the development of SIM for public services in Sukarame District using the Extreme Programming method has succeeded in creating a system that can manage population data, public complaints, and service letters effectively. The test results show that the accuracy of the system reaches 100%. The findings from these three studies show the importance of implementing SIM in various fields to improve the quality of public services.